Dehydrating agent composition and ammonia dehydration method

By using a dehydrating agent combined with nano alumina and composite adsorbent, the problem of poor dehydration effect of ammonia in the prior art is solved, and the preparation of high-purity ammonia is achieved, which reduces costs and meets environmental protection requirements.

CN119909645APending Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311419357.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-30
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

In the existing 6N electronic grade ammonia purification methods, the dehydration effect is poor, the cost is high, the operation is complex and the performance stability is insufficient.

Method used

A dehydrating agent combined with nano alumina and composite adsorbents (4A molecular sieve and 13X molecular sieve) is used to form a catalyst with dual adsorption function through mixing and tandem technology to achieve efficient ammonia dehydration.

Benefits of technology

The preparation of high-purity ammonia is achieved, with a water content of less than 100ppb, which reduces production costs, improves catalytic efficiency, and meets environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004520573860000081
    Figure BDA0004520573860000081
Patent Text Reader

Abstract

The invention relates to the technical field of gas purification, and discloses a dehydrating agent composition which is characterized by comprising nano aluminum oxide and a composite adsorbent, wherein the composite adsorbent comprises a 4A molecular sieve and a 13X molecular sieve; wherein the mass ratio of the nano aluminum oxide to the composite adsorbent is (1: 7)-(5: 1); the mass ratio of the 4A molecular sieve to the 13X molecular sieve is (1: 5)-(2: 1). The dehydrating agent composition has the characteristics of high specific surface area, better adsorption capacity, high catalytic efficiency, high dehydration rate, low cost, convenience in preparation, low toxicity and environment friendliness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gas purification, and in particular to a composition and an ammonia dehydration method in 6N electronic grade ammonia purification. Background Art

[0002] As a high-purity gas, 6N electronic grade ammonia is widely used in high-tech fields such as electronic components, semiconductors and optoelectronic device manufacturing. However, the preparation of 6N electronic grade ammonia involves the purification of ammonia liquid, among which dehydration is a crucial step, the purpose of which is to remove trace moisture in ammonia liquid to achieve higher purity requirements. Even a tiny amount of moisture can affect the purity of the gas and even cause problems such as component failure.

[0003] At present, the commonly used method for purifying 6N electronic grade ammonia is mainly through dehydration adsorption and drying. However, existing adsorbents, such as silica gel and activated carbon, have problems such as high cost, complex operation and poor performance stability.

[0004] Therefore, it is necessary to provide a dehydrating agent composition and an ammonia dehydration method with good dehydration effect, low cost and environmental protection. Summary of the invention

[0005] The purpose of the present invention is to overcome the problem of poor dehydration effect in the prior art and provide a dehydrating agent composition and an ammonia dehydration method with good dehydration effect, low cost and environmental protection.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a dehydrating agent composition, wherein the composition comprises: nano-alumina and a composite adsorbent;

[0007] Wherein, the composite adsorbent comprises: 4A molecular sieve and 13X molecular sieve;

[0008] Wherein, the mass ratio of the nano-alumina to the composite adsorbent is 1:7-4:1; the mass ratio of the 4A molecular sieve to the 13X molecular sieve is 1:5-1:1.

[0009] A second aspect of the present invention provides a method for dehydrating ammonia, the method comprising:

[0010] (1) contacting the ammonia gas to be dehydrated with nano-alumina to obtain a mixture of ammonia and a small amount of water vapor;

[0011] (2) contacting the mixture in step (1) with a composite adsorbent for a second time to obtain high-purity ammonia;

[0012] Wherein, the composite adsorbent comprises: 4A molecular sieve and 13X molecular sieve;

[0013] Wherein, the mass ratio of the nano-alumina to the composite adsorbent is 1:7-4:1;

[0014] Wherein, the mass ratio of the 4A molecular sieve to the 13X molecular sieve is 1:5-1:1.

[0015] Through the above technical solution, the beneficial effects of the present invention are:

[0016] (1) Economic cost: The present invention uses low-cost, readily available 4A and 13X molecular sieves as adsorbents and uses economical and efficient mixing and series connection technology, thereby greatly reducing the cost of preparing the catalyst. In addition, since the present invention uses nano-alumina, it has higher activity in the catalytic reaction, which can effectively improve the reaction efficiency and further reduce the production cost.

[0017] (2) Mixing and series connection technology: The present invention uses mixing and series connection technology to organically combine 4A and 13X molecular sieves with nano-alumina to form a catalyst with dual adsorption functions. Compared with the traditional method of using a single adsorbent or multiple adsorbents in parallel, the mixing and series connection technology of the present invention can improve the adsorption and catalytic efficiency, reduce production links and equipment, and reduce production costs.

[0018] (3) Composition: The ratio of 4A and 13X molecular sieves used in the adsorbent of the present invention is 1:3, which can more effectively remove pollutants during adsorption. At the same time, the ratio of nano-alumina to 4A-13X composite adsorbent in the catalyst is 1:5. This ratio can make the catalytic effect of nano-alumina more obvious and improve the catalytic efficiency. The combination of 4A and 13X is to form a more uniform adsorption layer to increase the dehydration efficiency and reduce the amount of adsorbent used. The introduction of alumina nanoparticles can further increase the adsorption capacity and stability of the adsorbent, improve the dehydration efficiency and reduce the regeneration cost of the adsorbent. In addition, this combined adsorbent can be used multiple times, has a long service life, and can also avoid the secondary pollution problem existing in other dehydration methods. At the same time, the adsorbent of nano-alumina has the characteristics of high specific surface area, good adsorption capacity, high catalytic efficiency, etc., which can effectively remove moisture and impurities in ammonia and improve its purity. It also has the advantages of low cost and convenient preparation.

[0019] (4) Environmental protection: The present invention uses low-toxic and environmentally friendly 4A and 13X molecular sieves as adsorbents, and nano-alumina as catalysts, which are non-toxic and harmless and meet environmental protection requirements. In addition, the present invention uses a catalyst with dual adsorption functions, which can not only effectively remove pollutants, but also convert pollutants into harmless substances, further reducing the impact on the environment.

[0020] Therefore, the innovative points of the present invention are mainly reflected in the mixing and series technology, the use of low-cost and readily available adsorbents, the application of nano-alumina and environmental protection. It can improve catalytic efficiency, reduce production costs, meet environmental protection requirements, and has great economic and social benefits. DETAILED DESCRIPTION

[0021] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0022] The first aspect of the present invention provides a dehydrating agent composition, wherein the composition comprises: nano-alumina and a composite adsorbent;

[0023] Wherein, the composite adsorbent comprises: 4A molecular sieve and 13X molecular sieve;

[0024] The mass ratio of the nano-alumina to the composite adsorbent is 1:7-4:1; the mass ratio of the 4A molecular sieve to the 13X molecular sieve is 1:5-1:1. When the mass ratios of the nano-alumina to the composite adsorbent and the 4A molecular sieve to the 13X molecular sieve are not within the above ranges, the technical effect of the water content of high-purity ammonia being less than 100 ppb (mass) cannot be achieved.

[0025] In some embodiments of the present invention, preferably, the mass ratio of the nano-alumina to the composite adsorbent is 1:6-3:1; the mass ratio of the 4A molecular sieve to the 13X molecular sieve is 1:4-1:1.

[0026] In some embodiments of the present invention, preferably, the silicon-aluminum ratio of the 4A molecular sieve is 1:2-2:1; preferably 2:3-3:2. When the silicon-aluminum ratio is less than 1:2, the adsorption sites of the 4A molecular sieve may not be sufficient to effectively adsorb water molecules in ammonia. The relatively low silicon-aluminum ratio in the 4A molecular sieve will lead to a scarcity of adsorption sites, thereby reducing the capture efficiency of water molecules. This will lead to a decrease in the removal efficiency of water molecules in ammonia, causing the water content in the resulting high-purity ammonia to increase, exceeding the required specifications, thereby reducing the effectiveness of the technology; when the silicon-aluminum ratio is greater than 2:1, the adsorption sites of the 4A molecular sieve may be saturated, and it may be easier to adsorb ammonia molecules in ammonia rather than water molecules. This will lead to a decrease in the selectivity of the molecular sieve, making it unable to effectively remove water molecules in ammonia. As a result, the resulting high-purity ammonia still contains a high amount of water and fails to meet specific specifications.

[0027] In some embodiments of the present invention, preferably, the specific surface area of ​​the 4A molecular sieve is 50-500m 2 / g; preferably 100-300m 2 / g. When the specific surface area of ​​the 4A molecular sieve is less than 50m 2 / g will result in a decrease in the surface area of ​​the adsorbent, which will limit the number of adsorption sites and thus reduce the adsorption of water molecules; when the specific surface area of ​​the 4A molecular sieve is greater than 500m 2 / g will result in more adsorption sites, but it may lead to competition between the adsorption sites, reducing the selective capture of water molecules. Therefore, the specific surface area of ​​4A molecular sieve should be within an appropriate range to achieve efficient dehydration.

[0028] In some embodiments of the present invention, preferably, the porosity of the 4A molecular sieve is 20-60%; preferably 30-50%. When the porosity of the 4A molecular sieve is less than 20%, the internal structure of the adsorbent may not provide enough space to accommodate and capture water molecules in ammonia; when the porosity of the 4A molecular sieve is greater than 60%, too much space may cause the gas to pass through the adsorption bed without sufficient contact, thereby reducing the adsorption efficiency of water molecules. Therefore, the porosity of the 4A molecular sieve should be within an appropriate range to provide optimal dehydration performance.

[0029] In some embodiments of the present invention, preferably, the silicon-aluminum ratio of the 13X molecular sieve is 1:2-2:1; preferably 2:3-3:2.

[0030] The interaction between the above parameters and their association with the dehydration process are critical, as they together determine the effective removal of water molecules from ammonia. Therefore, selecting these parameters within the specified range can ensure an efficient, economical and sustainable ammonia dehydration process.

[0031] In some embodiments of the present invention, preferably, the specific surface area of ​​the 13X molecular sieve is 100-600m 2 / g; preferably 200-400m 2 / g. When the specific surface area of ​​the 13X molecular sieve is less than 50-500m 2 / g will result in a decrease in the effective surface area of ​​the adsorbent, thereby reducing the number of adsorption sites and reducing the efficiency of adsorption of water molecules in ammonia. This will increase the content of water molecules in high-purity ammonia, which does not meet the required specifications; when the specific surface area of ​​the 13X molecular sieve is greater than 50-500m 2 / g will lead to increased competition between adsorption sites, thereby reducing the selective capture of water molecules. This will also lead to an increase in the content of water molecules in high-purity ammonia, which does not meet the specification requirements.

[0032] In some embodiments of the present invention, preferably, the porosity of the 13X molecular sieve is 20-60%; preferably 30-50%. When the porosity of the 13X molecular sieve is less than 20-60%, the space provided by the internal structure of the adsorbent is insufficient to accommodate and capture water molecules in the ammonia gas, thereby reducing the dehydration efficiency; when the porosity of the 13X molecular sieve is greater than 20-60%, too much space may cause the gas to pass through the adsorption bed without sufficient contact, thereby reducing the dehydration efficiency. This will also lead to an increase in the content of water molecules in the high-purity ammonia gas, which does not meet the specifications.

[0033] Therefore, the preferred range of the specific surface area and porosity of the 13X molecular sieve is to ensure that the dehydration effect is in the best state. Exceeding or falling below these ranges will result in high-purity ammonia gas not meeting specific specifications, thereby reducing the technical effectiveness of the present invention.

[0034] A second aspect of the present invention provides a method for dehydrating ammonia, the method comprising:

[0035] (1) contacting the ammonia gas to be dehydrated with nano-alumina to obtain a mixture of ammonia and a small amount of water vapor;

[0036] (2) contacting the mixture in step (1) with a composite adsorbent for a second time to obtain high-purity ammonia;

[0037] Wherein, the composite adsorbent comprises: 4A molecular sieve and 13X molecular sieve;

[0038] Wherein, the mass ratio of the nano-alumina to the composite adsorbent is 1:7-4:1;

[0039] Wherein, the mass ratio of the 4A molecular sieve to the 13X molecular sieve is 1:5-1:1.

[0040] In some embodiments of the present invention, preferably, the mass ratio of the nano-alumina to the composite adsorbent is 1:6-3:1; the mass ratio of the 4A molecular sieve to the 13X molecular sieve is 1:4-1:1.

[0041] In some embodiments of the present invention, preferably, in step (1), the volume fraction of ammonia in the mixture is 95-98%, and the volume fraction of water vapor is not higher than 0.5%. When the volume fraction of ammonia in the mixture is less than the above range, the purity of ammonia will be insufficient, which does not meet the technical effect required for high-purity ammonia; when the volume fraction of water vapor is less than the above range, the dehydration effect is poor, resulting in the water molecule content exceeding the specification. This adjustment helps to ensure the preparation of high-purity ammonia.

[0042] In some embodiments of the present invention, preferably, in step (1), the temperature of the first contact is 20-100°C, preferably 30-80°C; the pressure is 1-10atm, preferably 2-8atm; and the time is 1-30min, preferably 5-20min. When the temperature of the first contact is less than the above range, it may take longer to achieve effective dehydration because the adsorption rate is slower at low temperatures; when the temperature of the first contact is greater than the above range, it may cause unnecessary energy consumption; when the pressure of the first contact is less than the above range, it may take longer to achieve the same effect; when the pressure of the first contact is greater than the above range, it may lead to energy waste; when the time of the first contact is less than the above range, sufficient dehydration effect may not be achieved; when the time of the first contact is greater than the above range, resources may be wasted.

[0043] In some embodiments of the present invention, preferably, in step (2), the temperature of the second contact is 40-90°C; the pressure is 1-7 atm; and the time is 10-25 min. When the temperature of the second contact is less than the above range, it may take longer to achieve the preparation of high-purity ammonia; when the temperature of the second contact is greater than the above range, it may cause energy waste; when the pressure of the second contact is less than the above range, it may take longer to achieve the same effect, and when the pressure of the second contact is greater than the above range, it may cause energy waste; when the time of the second contact is less than the above range, it may not achieve a sufficient dehydration effect, and when the time of the second contact is greater than the above range, resources may be wasted.

[0044] The present invention will be described in detail below through examples. In the following examples, the high-purity dehydration rate parameter is measured by an infrared moisture meter; the nano-alumina raw material is a commercial product of Guangzhou Metallurgy Co., Ltd.; the 4A molecular sieve raw material is a commercial product of Zhuoran Environmental Protection Technology Co., Ltd.; and the 13X molecular sieve raw material is a commercial product of Zhuoran Environmental Protection Technology Co., Ltd.

[0045] Example 1

[0046] The 6N electronic grade ammonia to be dehydrated is first contacted with nano-alumina, and the gas flow rate is controlled at 150mL / min. The temperature of the first contact is 50°C, the pressure is 1atm, and the time is 15min, and a mixture of ammonia and a small amount of water vapor is obtained. The mixture is second contacted with 4A molecular sieve and 13X molecular sieve (composite adsorbent, mass ratio is 1:3), the silicon-aluminum ratio of the 4A molecular sieve and the 13X molecular sieve is 1:1, the mass ratio of nano-alumina to the composite adsorbent is 1:5, the temperature of the second contact is 70°C, the pressure is 3atm, and the time is 20min, and high-purity ammonia is obtained, and its water content is 47.5ppb.

[0047] Example 2

[0048] High-purity ammonia was prepared in the same manner as in Example 1, except that the mass ratio of nano-alumina to the composite adsorbent was 1:1, and high-purity ammonia was obtained, the water content of which was 97.3 ppb.

[0049] Example 3

[0050] High-purity ammonia was prepared in the same manner as in Example 1, except that the mass ratio of nano-alumina to the composite adsorbent was 1:3, and high-purity ammonia was obtained, the water content of which was 109.2 ppb.

[0051] Example 4

[0052] High-purity ammonia was prepared in the same manner as in Example 1, except that the mass ratio of nano-alumina to the composite adsorbent was 3:1, and high-purity ammonia was obtained, the water content of which was 118.4 ppb.

[0053] Example 5

[0054] High-purity ammonia was prepared in the same manner as in Example 1, except that the mass ratio of 4A molecular sieve to 13X molecular sieve in the composite adsorbent was 1:5, and high-purity ammonia was obtained, the water content of which was 120 ppb.

[0055] Comparative Example 1

[0056] High-purity ammonia was prepared in the same manner as in Example 1, except that the mass ratio of nano-alumina to the composite adsorbent was 5:1, and high-purity ammonia was obtained, the water content of which was 130.2 ppb.

[0057] Comparative Example 2

[0058] High-purity ammonia was prepared in the same manner as in Example 1, except that the mass ratio of 4A molecular sieve to 13X molecular sieve in the composite adsorbent was 2:1, and high-purity ammonia was obtained, the water content of which was 210 ppb.

[0059] The mass ratios of nano-alumina and composite adsorbent and the water content of high-purity ammonia in various embodiments and comparative examples are summarized in Table 1.

[0060] Table 1

[0061]

[0062] It can be seen from the results in Table 1 that the embodiments using the technical solution of the present invention have a beneficial effect in terms of ammonia dehydration rate. By comparing the dehydration rates of other embodiments and comparative examples with those of Example 1, it can be seen that when the mass ratio of nano-alumina to the composite adsorbent is 1:5 and the mass ratio of 4A molecular sieve to 13X molecular sieve in the composite adsorbent is 1:3, the best ammonia dehydration effect can be obtained.

[0063] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A dehydrating agent composition, characterized in that: The composition comprises: nano alumina and a composite adsorbent; Wherein, the composite adsorbent comprises: 4A molecular sieve and 13X molecular sieve; The mass ratio of the nano-alumina to the composite adsorbent is 1:7-4:1; the mass ratio of the 4A molecular sieve to the 13X molecular sieve is 1:5-1:

1.

2. The dehydrating agent composition according to claim 1, wherein The mass ratio of the nano-alumina to the composite adsorbent is 1:6-3:1; the mass ratio of the 4A molecular sieve to the 13X molecular sieve is 1:4-1:

1.

3. The dehydrating agent composition according to claim 1 or 2, wherein The silicon-aluminum ratio of the 4A molecular sieve is 1:2-2:1; preferably 2:3-3:

2.

4. The dehydrating agent composition according to any one of claims 1 to 3, wherein The specific surface area of ​​the 4A molecular sieve is 50-500m 2 / g; preferably 100-300m 2 / g.

5. The dehydrating agent composition according to any one of claims 1 to 4, wherein The porosity of the 4A molecular sieve is 20-60%, preferably 30-50%.

6. The dehydrating agent composition according to any one of claims 1 to 5, wherein The silicon-aluminum ratio of the 13X molecular sieve is 1:2-2:1; preferably 2:3-3:

2.

7. The dehydrating agent composition according to any one of claims 1 to 6, wherein: The specific surface area of ​​the 13X molecular sieve is 100-600m 2 / g; preferably 200-400m 2 / g.

8. The dehydrating agent composition according to any one of claims 1 to 7, wherein The porosity of the 13X molecular sieve is 20-60%, preferably 30-50%.

9. A method for dehydrating ammonia, the method comprising: (1) contacting the ammonia gas to be dehydrated with nano-alumina for the first time to obtain an ammonia-containing mixture with a water vapor volume fraction of not more than 0.5%; (2) contacting the mixture with a composite adsorbent for a second time to obtain high-purity ammonia; Wherein, the composite adsorbent comprises: 4A molecular sieve and 13X molecular sieve; Wherein, the mass ratio of the nano-alumina to the composite adsorbent is 1:7-4:1; Wherein, the mass ratio of the 4A molecular sieve to the 13X molecular sieve is 1:5-1:

1.

10. The method according to claim 9, wherein: The mass ratio of the nano-alumina to the composite adsorbent is 1:6-3:1; the mass ratio of the 4A molecular sieve to the 13X molecular sieve is 1:4-1:

1.

11. The method according to claim 9 or 10, wherein: In step (1), the volume fraction of ammonia in the mixture is 95-98%.

12. The method according to any one of claims 9 to 11, wherein: In step (1), the temperature of the first contact is 20-100°C, preferably 30-80°C; the pressure is 1-10atm, preferably 2-8atm; and the time is 1-30min, preferably 5-20min.

13. The method according to any one of claims 9 to 12, wherein: In step (2), the temperature of the second contact is 40-90°C; the pressure is 1-7 atm; and the time is 10-25 min.